2019
DOI: 10.1055/s-0039-1688760
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Immediate versus Delayed Sternal Reconstruction with Pectoralis Major Advancement Versus Turnover Muscle Flaps

Abstract: Background The pectoralis major muscle flap is a versatile reconstructive option for deep sternal wound infections (DSWI). The timing and surgical technique of bilateral pectoralis major muscle advancement flaps versus unilateral pectoralis major muscle turnover and unilateral pectoralis major muscle advancement flap on patient outcomes remain to be elucidated. The purpose of this investigation was to compare timing, immediate versus delayed reconstruction, and the surgical technique in patients with deep ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The redistribution of forces helps prevent dehiscence, reinfections, and fistulas, and is the main reason for reducing postoperative morbidity, mortality, and length of postoperative hospitalization compared with those reported in the literature. 3,[28][29][30][31]…”
Section: Discussionmentioning
confidence: 99%
“…The redistribution of forces helps prevent dehiscence, reinfections, and fistulas, and is the main reason for reducing postoperative morbidity, mortality, and length of postoperative hospitalization compared with those reported in the literature. 3,[28][29][30][31]…”
Section: Discussionmentioning
confidence: 99%
“…16 Multiple studies have demonstrated the benefit of early referral and reconstruction after diagnosis of a sternal wound, with decreased morbidity, Plastic and Reconstructive Surgery • August 2021 length of stay, mortality, and resource use. 2,5,17 However, these studies generally do not take into account the timing from cardiac surgery to sternal wound intervention. Many of our patients present initially with only drainage or a sternal click, but more than 60 percent have positive deep wound or bone cultures and more extensive findings on operative exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have demonstrated loss of shoulder function with disinsertion of the pectoralis muscle either as a turnover flap or as an advancement flap. 22 , 30 32 On the other hand, Kamel et al 23 showed that patients who had pectoralis advancement flaps had less tissue necrosis than those who had turnover flaps. Furthermore, the pectoralis turnover flap relies on blood supply from the internal mammary artery.…”
Section: Discussionmentioning
confidence: 99%